Annual energy and environment analysis of solarized steam injection gas turbine (STIG) cycle for Indian regions. (5th February 2016) - Selwynraj, A. Immanuel; Iniyan, S.; Suganthi, L.; Livshits, Maya; Polonsky, Guy; Kribus, Abraham
Highlights: Study on the influence of local climatic conditions on solar STIG cycle is presented. The annual solar to electricity efficiency ranges between 11.2 and 17.1% and the solar fraction ranges 9.3–41.7%. The range of annual specific CO2 emission is 312–408 kg/MWh and incremental CO2 avoidance is 4.2–104 kg/MWh. The levelized tariff (LT) is 0.2–0.23 /kWh, and the solar levelized tariff (SLT) ranges from 0.11 to 0.27 /kWh. Abstract: The solarized steam injection gas turbine (STIG) cycle uses both the fuel and solar heat simultaneously for power generation. The annual thermodynamic performances of the cycle for sites in India with local climatic conditions such as ambient temperature, relative humidity and availability of direct normal irradiance (DNI) to the solar concentrators under two modes of constant and variable power are presented in this paper. The results reveal that the solar to electricity efficiency of solar hybrid STIG plant with a simple parabolic trough collector (PTC) is similar to existing solar thermal technologies, and also higher solar share is obtained. The study also reveals that the annual CO2 emission is similar to combined cycle plants and lower than gas turbine technologies. The incremental CO2 avoidance is also computed due to solar participation. The annual values of exergetic solar fraction and exergetic efficiency at Indore are higher than Jaipur. Results of an improved economic assessment show that the levelized tariff (LT) of solar hybrid STIG plant is 0.2–0.23 /kWh and the levelized tariff (solar only) or solar levelized tariff (SLT) of solar STIG plant ranges from 0.11 to 0.27 /kWh for both constant and variable power scenarios.